2008
DOI: 10.1177/0267659108097880
|View full text |Cite
|
Sign up to set email alerts
|

The minimized extracorporeal circulation system causes less inflammation and organ damage

Abstract: The minimized extracorporeal circulation system (MECC) is being used to reduce priming volume and blood/polymer contact during cardiac procedures. In this study, we evaluated the efficacy and potential advantages of the system in coronary artery bypass graft (CABG) patients. We included two groups of patients destined for CABG in a prospective, randomized study: Group A was operated on the usual pump (n = 30) while Group B was operated using the MECC (n = 50). Pre-operative demographics, intra-operative times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 20 publications
(25 reference statements)
2
27
1
1
Order By: Relevance
“…Other studies revealed significant decreased IL-8 levels using the MECC system. 19,20 In contrast, this study did not show lower levels of inflammatory markers such as IL-6, IL-8, and TNF-alpha in both mini-CPB groups compared with CCPB. These re- sults are supported by other groups 20,24,25 and might be attributed to significant longer OR, ECC, and cross-clamp time in both mini-CPB groups compared with CCPB.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Other studies revealed significant decreased IL-8 levels using the MECC system. 19,20 In contrast, this study did not show lower levels of inflammatory markers such as IL-6, IL-8, and TNF-alpha in both mini-CPB groups compared with CCPB. These re- sults are supported by other groups 20,24,25 and might be attributed to significant longer OR, ECC, and cross-clamp time in both mini-CPB groups compared with CCPB.…”
Section: Discussioncontrasting
confidence: 86%
“…Other studies reporting on mini-CPB systems support these results. 17,19,32,36 Limitations In this study, all patients without the indicated exclusion criteria undergoing elective coronary artery bypass grafting were included. Because our hospital is a university center and surgical training is performed, these elective low-risk patients are operated by either experienced or inexperienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several investigators have demonstrated better postoperative outcome in terms of reduced inflammatory response and postoperative blood loss. [12][13][14][15] However, to our knowledge, there are no studies that include PF1+2, TaTc formation and clotting evaluation by thromboelastography (TEG). The aim of this study was to evaluate the impact of either conventional ECC (cECC) or MECC in terms of coagulation disorders, blood loss and early postoperative lung function in patients undergoing CABG.…”
Section: Introductionmentioning
confidence: 99%
“…(Level of Evidence: B) 2. High thoracic epidural analgesia may be considered to improve lung function after CABG(37,1202). (Level of Evidence: B)…”
mentioning
confidence: 99%